Genetic screening in adolescents with steroid-resistant nephrotic syndrome - Lipska-Ziętkiewicz, Beata S.; Trautmann, Agnes; Schaefer, Franz (Kidney international, 2013)
Genetic screening paradigms for congenital and infantile nephrotic syndrome are well established; however, screening in adolescents has received only minor attention. To help rectify this, we analyzed an unselected adolescent cohort of the international PodoNet registry to develop a rational screening approach based on 227 patients with nonsyndromic steroid-resistant nephrotic syndrome aged 10-20 years. Of these, 21% had a positive family history. Autosomal dominant cases were screened for WT1, TRPC6, ACTN4, and INF2 mutations. All other patients had the NPHS2 gene screened, and WT1 was tested in sporadic cases. In addition, 40 sporadic cases had the entire coding region of INF2 tested. Of the autosomal recessive and the sporadic cases, 13 and 6%, respectively, were found to have podocin-associated nephrotic syndrome, and 56% of them were compound heterozygous for the nonneutral p.R229Q polymorphism. Four percent of the sporadic and 10% of the autosomal dominant cases had a mutation in WT1. Pathogenic INF2 mutations were found in 20% of the dominant but none of the sporadic cases. In a large cohort of adolescents including both familial and sporadic disease, NPHS2 mutations explained about 7% and WT1 4% of cases, whereas INF2 proved relevant only in autosomal dominant familial disease. Thus, screening of the entire coding sequence of NPHS2 and exons 8-9 of WT1 appears to be the most rational and cost-effective screening approach in sporadic juvenile steroid-resistant nephrotic syndrome.